I will love you forever - Miyanishi, Tatsuya, 1956- (Miyanishi, Tatsuya, 1956- Tyrannosaurus series, 2017)
Finding an egg in the forest, a Maiasaura takes care of it, and the baby Tyrannosaurus that hatches, but eventually the Tyrannosaurus discovers what it really is.